FAKTOR – FAKTOR YANG MEMPENGARUHI PEMILIHAN MKJP DAN NON MKJP PADA PUS DI RSU AL ISLAM H.M MAWARDI KRIAN – SIDOARJO - Yuni Yastutik, Iryani; Imam, Nurul (LPPM STIKES HUSADA JOMBANG, 2022)
Indonesia is one of the rapidly growing countries and the relatively high death of its mother.One of the government's attempts at suppressing birth is through family planning.This family program aims to speed up the population and reduce the number of mothers' deaths by preventing pregnancies in young people, setting the pregnancy distance, and stopping pregnancy (Yulidasari dkk, 2015).Modern contraceptive methods are divided into 3: long-term contraceptive methods (IUD and Implan), non-long-term contraceptive methods (oral contraceptive, condom, spermicide, and injection) and permanent contraceptive methods (MOW and MOP).This long-term non-contraceptive method is more common than the long-term contraceptive method although it is more efficient, expensive and well tolerated.The effectiveness of non-MKJP depends on user characteristics such as the level of education that affects their knowledge.The purpose of this research is to identify the level of PUS knowledge, the selection of MKJP and Non-MKJP on PUS, and analyse the level of knowledge relationship with the selection of MKJP and Non-MKJP on PUS at the RSU Al-Islam H.M Mawardi sidoarjo.The research method used in this research is observational analytics with case control design approaches.Sampling techniques used are simple random sampling techniques.Hasil penelitian ini adalah 55 seluruh PUS akseptor KB diRSU Al-Islam H.M Mawardi sidoarjo. Based on the results of the statistical test, p value = 0.013 is obtained, which means there is a significant relationship between the level of knowledge and the choice of MKJP and Non-MKJP on the PUS RSU Al-Ioslam H.M Mawardi Sidoarjo.The conclusion from this study is that the majority of responders using PWN have good knowledge (43.7%) and the majority of responders using non-PWN have less knowledge (62.5%).There is a significant relationship between the level of knowledge and the choice of MKJP and Non-MKJP in PUS at the Al-Islamic RSU H.M Mawardi Sidoarjo.Response knowledge can be enhanced through education and decimation with more intensive advisory methods.Through evidence-based counseling and containing up-to-date information, health care provides women's pad opportunities to choose the type of contraceptive that fits her condition and needs.